Camp literature. Introduction - Morawiec, Arkadiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
This article includes a terminological discussion regarding the notion of camp literature. Within Polish literary science, it is usually applied to literature raising the topic of German Nazi camps, particularly concentration camps and death camps, and, though less often, to Soviet camps, particularly forced labour camps. Yet the definition has proved to be excessively narrow. It should also cover, previously less studied, works of Polish literature regarding, i.a. the Polish concentration camp in Bereza Kartuska, the communist labour camps established in post-WWII Poland, and the Spanish concentration camp in Miranda de Ebro. The notion camp literature could also be applied to works devoted to internment camps, POW camps, or even ghettoes.